Response of Sesame to Selected Herbicides Applied Early in the Growing Season - W. James Grichar; Jack J. Rose; Peter A. Dotray; Todd A. Baughman; D. Ray Langham; Kaisa Werner; Muthu Bagavathiannan (International Journal of Agronomy)
Growth chamber experiments were conducted to evaluate the response of sesame to PRE and POST applications of soil residual herbicides. PRE applications of acetochlor and S-metolachlor at 1.26 and 1.43 kg ai·ha−1 showed little or no sesame injury (0 to 1%) 4 wks after herbicide treatments (WAT). POST treatments of acetochlor and trifluralin made 3 wks after planting (WAP) resulted in greater sesame injury (40%) compared to applications at bloom (18%). Field studies were conducted in Texas and Oklahoma during the 2014 and 2015 growing seasons to determine sesame response to clethodim, diuron, fluometuron, ethalfluralin, quizalofop-P, pendimethalin, pyroxasulfone, trifluralin, and trifloxysulfuron-sodium applied 2, 3, or 4 weeks after planting (WAP). Late-season sesame injury with the dinitroaniline herbicides consisted of a proliferation of primary branching at the upper nodes of the sesame plant (in the shape/form of a broom). Ethalfluralin and trifluralin caused more “brooming” effect than pendimethalin. Some yield reductions were noted with the dinitroaniline herbicides. Trifloxysulfuron-sodium caused the greatest injury (up to 97%) and resulted in yield reductions from the untreated check. Early-season diuron injury (leaf chlorosis and necrosis) decreased as application timing was delayed, and late-season injury was virtually nonexistent with only slight chlorosis (<4%) still apparent on the lower leaves. Sesame yield was not consistently affected by the diuron treatments. Fluometuron caused early-season injury (stunting/chlorosis), and a reduction of yield was observed at one location. Pyroxasulfone applied 2 WAP caused up to 25% sesame injury (stunting) but did not result in a yield reduction. Quizalofop-P caused slight injury (<5%) and no reduction in yield.